Izobraževanje v digitalnem svetu - Krašna, Marjan (2015)
Education in the Digital World. The book brings to the field of education in today's digital world new insights that have emerged over the years of researching, creating and developing modern e-learning materials. It will be of interest to creative teachers at all levels of education, as well as students - future teachers. At the same time, the book will be a useful guide for all authors and developers of e-learning materials.